Dealing with fuel contaminants in biogas-fed solid oxide fuel cell (SOFC) and molten carbonate fuel cell (MCFC) plants: Degradation of catalytic and electro-catalytic active surfaces and related gas purification methods. (July 2017) - Lanzini, Andrea; Madi, Hossein; Chiodo, Vitaliano; Papurello, Davide; Maisano, Susanna; Santarelli, Massimo; Van herle, Jan
Abstract: Fuel cell and hydrogen technologies are re-gaining momentum in a number of sectors including industrial, tertiary and residential ones. Integrated biogas fuel cell plants in wastewater treatment plants and other bioenergy recovery plants are nowadays on the verge of becoming a clear opportunity for the market entry of high-temperature fuel cells in distributed generation (power production from a few kW to the MW scale). High-temperature fuel cell technologies like molten carbonate fuel cells (MCFCs) and solid oxide fuel cells (SOFCs) are especially fit to operate with carbon fuels due to their (direct or indirect) internal reforming capability. Especially, systems based on SOFC technology show the highest conversion efficiency of gaseous carbon fuels (e.g., natural gas, digester gas, and biomass-derived syngas) into electricity when compared to engines or gas turbines. Also, lower CO2 emissions and ultra-low emissions of atmospheric contaminants (SOX, CO, VOC, especially NOX ) are generated per unit of electricity output. Nonetheless, stringent requirements apply regarding fuel purity. The presence of contaminants within the anode fuel stream, even at trace levels (sometimes ppb levels) can reduce the lifetime of key components like the fuel cell stack and reformer. In this work, we review the complex matrix (typology and amount) of different contaminants that is found in different biogas types (anaerobic digestion gas and landfill gas). We analyze the impact of contaminants on the fuel reformer and the SOFC stack to identify the threshold limits of the fuel cell system towards specific contaminants. Finally, technological solutions and related adsorbent materials to remove contaminants in a dedicated clean-up unit upstream of the fuel cell plant are also reviewed.